Deconstructing Dogmatic Narratives: An Effort to Recontextualize Islamic Education Material for the Critical Generation - Faridatul Jannah; Umar Manshur; Ach Rizquha (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2025)
Islamic Religious Education (PAI) in schools is often trapped in a dogmatic and textual approach, which is less able to accommodate the social and intellectual dynamics of students. This study aims to explore efforts to recontextualize PAI materials by adapting religious teachings to the context of students' social, cultural, and intellectual lives, in order to improve their understanding, engagement, and critical thinking skills. The method used in this study is a qualitative case study approach, conducted in a junior high school in Probolinggo Regency, involving in-depth interviews, observation, and data analysis. The research findings indicate that the recontextualization of PAI materials successfully created a more inclusive and reflective learning climate, increased student enthusiasm, and encouraged them to connect religious teachings with contemporary social issues. This study contributes to the development of religious education theory, by offering a new approach to PAI learning that is more applicable and relevant. The practical implication is the importance of developing more contextual and interactive teaching methods.